Editorial for PCCP themed issue "Developments in Density Functional Theory". Issue 31 (13th July 2016) - van Leeuwen, Robert; Neugebauer, Johannes; Visscher, Lucas; Bickelhaupt, F. Matthias
Abstract : This issue provides an overview of the state-of-the-art of DFT, ranging from mathematical and software developments, via topics in chemical bonding theory, to all kinds of molecular and material properties. Through this issue, we also celebrate the enormous contributions that Evert Jan Baerends has made to this field.